Reconstructing Howard Gardner’s Theory of Multiple Intelligences within Islamic Educational Psychology: Toward a Model of Insan Kamil - Firdosi, Akh. Fad; Rohimah, Siti (El-Rusyd, 2026)
This study aims to reconstruct Howard Gardner’s theory of Multiple Intelligences within the perspective of Islamic Educational Psychology through a library research approach based on conceptual analysis and qualitative content analysis. Data were collected from Gardner’s primary works, literature on Islamic Educational Psychology, and national and international scholarly articles published between 2020 and 2026. The findings indicate that Gardner’s theory of Multiple Intelligences aligns with the concept of fitrah, as both acknowledge the diversity of human potential. However, Gardner’s framework remains oriented toward a humanistic paradigm that places self-actualization as the ultimate goal, and thus does not fully accommodate the dimensions of tauhid, spirituality, and morality. The reconstruction integrates the concepts of fitrah, ‘aql, qalb, ruh, and akhlaq into a paradigm that positions fitrah as the foundation, Gardner’s eight intelligences as basic potentials, and the integration of intellectual, spiritual, emotional, and moral dimensions as mechanisms of development, with insan kamil as the ultimate goal of education. This model expands Gardner’s theory while providing a conceptual foundation for the development of curriculum, learning strategies, and assessment in Islamic Education that is more holistic and oriented toward tauhidic values.